Being connected to nature, reindeer, and family: findings from a photovoice study on well-being among older South Sámi people - Ness, Tove Mentsen; Munkejord, Mai Camilla (International Journal of Circumpolar Health, 2021)
In this paper, we examine the perceptions of well-being among older South Sámi people with various experiences from reindeer herding by use of a method called photovoice. Eleven participants, including six men and five women aged 67–84 years, agreed to take photos of situations, things, or persons that made them feel a sense of well-being . When the researcher collected the photos, the participants were invited to tell their stories related to each photo. In the thematic analysis of the photos, three main themes emerged: a) well-being through connection to nature, b) well-being through connection to the reindeer, and c) well-being through connection to the family. In conclusion, we argue that if healthcare professionals are to enhance the well-being of care receivers – in this case older people with South Sami background from reindeer-herding families – they must consider the care receiver’s life story and what constitutes well-being for the individual person.